Mean Dietary Salt Intake in Urban and Rural Areas in India: A Population Survey of 1395 Persons - Johnson, Claire (J Am Heart Assoc, 2017)
BACKGROUND: The scientific evidence base in support of population‐wide salt reduction is strong, but current high‐quality data about salt intake levels in India are mostly absent. This project sought to estimate daily salt consumption levels in selected communities of Delhi and Haryana in north India and Andhra Pradesh in south India. METHODS AND RESULTS: In this study, 24‐hour urine samples were collected using an age‐ and sex‐stratified sampling strategy in rural, urban, and slum areas. Salt intake estimates were made for the overall population of each region and for major subgroups by weighting the survey data for the populations of Delhi and Haryana, and Andhra Pradesh. Complete 24‐hour urine samples were available for 637 participants from Delhi and Haryana and 758 from Andhra Pradesh (65% and 68% response rates, respectively). Weighted mean population 24‐hour urine excretion of salt was 8.59 g/day (95% CI 7.68–9.51) in Delhi and Haryana and 9.46 g/day (95% CI 9.06–9.85) in Andhra Pradesh (P=0.097). Estimates inflated to account for the minimum likely nonurinary losses of sodium provided corresponding estimates of daily salt intake of 9.45 g/day (95% CI 8.45–10.46) and 10.41 g/day (95% CI 9.97–10.84), respectively. CONCLUSIONS: Salt consumption in India is high, with mean population intake well above the World Health Organization recommended maximum of 5 g/day. A national salt reduction program would likely avert much premature death and disability.